Insights into gene expression responses to infections in teleosts using microarray data: a systematic review. (8th July 2020) - Caruffo, Mario; Mandakovic, Dinka; Cabrera, Pablo; Pacheco, Igor; Montt, Liliana; Chávez‐Báez, Ignacio; Mejías, Madelaine; Vera‐Tamargo, Francisca; Perez‐Valenzuela, Javiera; Carrasco‐Labra, Alonso; Pulgar, Rodrigo
Abstract: The rapid growth of production in aquaculture in the last decades has brought unwanted consequences affecting fish health and increasing the susceptibility to different infections. This systematic review aimed to analyse and summarize the current knowledge of gene expression responses to infectious diseases in teleosts using viruses, bacteria, fungi and parasites as agents through published microarray data. We conducted searches in electronic databases, including PubMed, Web of Science and SCOPUS until 1 May 2019. We identified 862 citations across databases and manual searches. After removing duplicates, we screened 455 unique references using titles and abstracts, of which 262 proved potentially eligible and evaluated using full text. A total of 79 articles proved eligible for this review. From the articles retrieved, we examined 261 different experiments (or 'studies') and more than a hundred thousand differentially expressed genes (DEGs). This systematic review represents the first catalogue of genes (and their associated processes) that differentially transcribe in different teleost species (13 species) due to infections generated by a large variety of pathogens (38 types). Although the obtained gene expression results are in considerable measure associated with expected immune response, other genes showed surprising significant transcriptional outcomes that may unravel unknown functions related to fish infections. This type of investigations facilitates the visualization of existing gaps in researches that may inspire future analysis in non‐traditional but relevant host or pathogen species.